Polarization switching behavior of one-axis-oriented lead zirconate titanate films fabricated on metal oxide nanosheet layer. (19th September 2017) - Uchida, Hiroshi; Ichinose, Daichi; Shiraishi, Takahisa; Shima, Hiromi; Kiguchi, Takanori; Akama, Akihiko; Nishida, Ken; Konno, Toyohiko J.; Funakubo, Hiroshi
Abstract: For the application of electronic devices using ferroelectric/piezoelectric components, one-axis-oriented tetragonal Pb(Zr0.40 Ti0.60 )O3 (PZT) films with thicknesses of up to 1 µm were fabricated with the aid of a Ca2 Nb3 O10 nanosheet (ns-CN) template for preferential crystal growth for evaluating their polarization switching behavior. The ns-CN template was supported on ubiquitous silicon (Si) wafer by a simple dip coating technique, followed by the repetitive chemical solution deposition (CSD) of PZT films. The PZT films were grown successfully with preferential crystal orientation of PZT(100) up to the thickness of 1020 nm. The (100)-oriented PZT film with ∼1 µm thickness exhibited unique polarization behavior of ferroelectric polarization, i.e., a marked increase in remanent polarization ( P r ) up to approximately 40 µC/cm 2 induced by domain switching under high electric field, whereas the film with a lower thickness showed only a lower P r of approximately 11 µC/cm 2 even under a high electric field. The ferroelectric property of the (100)-oriented PZT film after domain switching on ns-CN/Pt/Si can be comparable to those of (001)/(100)-oriented epitaxial PZT films.